FEMINIST APPROACHES TO LINGUISTIC STUDIES (Ta'limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2024)
ABSTRACT Feminist approaches to linguistic studies critically examine how language reflects and perpetuates gender inequalities and power dynamics. Rooted in feminist theory, these approaches challenge traditional linguistic practices that often marginalize or silence women and other gender minorities. Feminist linguistics explores how language both constructs and reinforces gendered identities, highlighting issues such as sexism in language, gendered communication styles, and the intersectionality of language with race, class, and sexuality. It critiques the dominant patriarchal linguistic norms and promotes more inclusive, equitable linguistic practices that recognize the diversity of gender experiences. Key areas of focus include the study of gendered language features like pronouns, titles, and speech patterns, as well as the social implications of language in different contexts. Feminist linguists also explore the ways in which language can be a tool for resistance, empowerment, and social change. By analyzing the relationship between language and gender, feminist linguistics seeks to transform both the academic study of language and the real-world use of language to foster equality and inclusivity.